Stabilization of human telomeric RNA G-quadruplex by the water-compatible optically pure and biologically-active metallohelices - Malina, Jaroslav; Scott, Peter; Brabec, Viktor (Scientific reports, 2020)
RNA G-quadruplexes have been suggested to play key roles in fundamental biological processes and are linked to human diseases. Thus, they also represent good potential therapeutic targets. Here, we describe, using the methods of molecular biophysics, interactions of a series of biologically-active supramolecular cationic metallohelices with human telomeric RNA G-quadruplex. We demonstrate that the investigated metallohelices bind with a high affinity to human telomeric RNA G-quadruplex and that their binding selectivity considerably differs depending on the dimensions and overall shape of the metallohelices. Additionally, the investigated metallohelices inhibit DNA synthesis on the RNA template containing four repeats of the human telomeric sequence by stabilizing the RNA G-quadruplex structure. Collectively, the results of this study suggest that stabilization of RNA sequences capable of G-quadruplex formation by metallohelices investigated in this work might contribute to the mechanism of their biological activity.
Keywords: telomery; konformace nukleové kyseliny; G-kvadruplexy; DNA; lidé; G-Quadruplexes; Telomere; Nucleic Acid Conformation; RNA; Humans